Retrospective Review of Flexible Bronchoscopy in Pediatric Cancer Patients - Ahmad, Ali H.; Brown, Brandon D.; Andersen, Clark R.; Mahadeo, Kris M.; Petropolous, Demetrios; Cortes, José A.; Razvi, Shehla; Gardner, Mary Katherine; Ewing, Linette J.; Mejia, Rodrigo E. (Frontiers in Oncology, 2021)
The use of flexible bronchoscopy (FB) with bronchoalveolar lavage (BAL) to diagnose and manage pulmonary complications has been shown to be safe in adult cancer patients, but whether its use is safe in pediatric cancer patients remains unclear. Thus, to describe the landscape of FB outcomes in pediatric cancer patients and to help define the populations most likely to benefit from the procedure, we undertook a retrospective review of FBs performed in patients younger than 21 years treated at our institution from 2002 to 2017. We found that a greater volume of total fluid instilled during BAL was significantly associated with increased probabilities of positive BAL culture (p=0.042), positive bacterial BAL culture (p=0.037), and positive viral BAL culture (p=0.0496). In more than half of the FB cases, findings resulted in alterations in antimicrobial treatment. Our study suggests that for pediatric cancer patients, FB is safe, likely provides diagnostic and/or therapeutic benefits, and has implications for treatment decisions.